Mucosal large cell neuroendocrine carcinoma of the head and neck regions in Japanese patients: a distinct clinicopathological entity. Issue 8 (20th June 2012) - Kusafuka, Kimihide; Abe, Masato; Iida, Yoshiyuki; Onitsuka, Tetsuro; Fuke, Tomohito; Asano, Rei; Kamijo, Tomoyuki; Nakajima, Takashi
Abstract : Backgrounds: Large cell neuroendocrine carcinoma (LCNEC) is well-known as a lung cancer subtype. This study assessed the prevalence of head and neck mucosal LCNEC (M-LCNEC). Methods: M-LCNEC was studied clinically, histologically and immunohistochemically. Results: Of 814 surgically resected cases of mucosal head and neck carcinoma, only eight cases (0.98%; all men, mean age 64.6 years) were rediagnosed as M-LCNEC. They occurred in the oropharynx (n=3), larynx (n=4) and hypopharynx (n=1). Seven of the cases had regional lymph node metastases and four resulted in death. Histologically, M-LCNEC had a sheet-like trabacular organoid growth pattern of relatively large basaloid cells in which central necrosis, rosette formation, peripheral palisading and high mitotic figures were evident. M-LCNEC was immunopositive for two or three neuroendocrine markers (CD56, chromogranin-A and synaptophysin). All cases showed high proliferative activity. Conclusion: M-LCNEC in the head and neck regions is a distinct histopathological entity whose positivity for neuroendocrine markers makes its diagnosis important. As about half of the patients died of the disease, M-LCNEC has a relatively poor prognosis.